Effect of Organic Nutrient Management on Growth Parameters of Knol-Khol (Brassica Oleracea L. Var. Gongylodes) Under Bundelkhand Conditions (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The present investigation was carried out during the Rabi season of 2026 to evaluate the effect of different organic nutrient sources on the growth performance of knol-khol (Brassica oleracea L. var. gongylodes) under Bundelkhand conditions. The Organic Agriculture Farm, Karguan Ji, Bundelkhand University, Jhansi, under a semi-arid subtropical climate on sandy loam soil with neutral to slightly alkaline pH (7.48) and medium fertility status. The initial soil contained 0.48% organic carbon, 236.5 kg ha⁻¹ available nitrogen, 19.2 kg ha⁻¹ available phosphorus, and 247.8 kg ha⁻¹ available potassium, providing suitable conditions for evaluating organic nutrient management. The uniform soil fertility and favorable climatic conditions ensured reliable treatment comparisons, as reflected by the low coefficients of variation and highly significant treatment effects observed in the ANOVA. The experiment was laid out in a Randomized Block Design (RBD) comprising eight treatments with three replications. The treatments consisted of Panchagavya (4%), Jivamrita (20%), Vermiwash (1:5 dilution), their different combinations, Recommended Dose of Fertilizers (RDF: 120:30:30 kg NPK ha⁻¹), and an untreated control. Growth parameters such as plant height, number of leaves per plant, and leaf area were recorded at harvest. The results indicated significant differences among treatments. The combined application of Panchagavya (4%) and Jivamrita (20%) (T4) recorded the highest plant height (35.6 cm), maximum number of leaves per plant (18.7), and largest leaf area (400.5 cm²), followed by Panchagavya (4%) + Vermiwash (1:5 dilution) (T5). The control treatment recorded the lowest values for all growth attributes. The superior performance of integrated organic treatments was attributed to improved nutrient availability, enhanced microbial activity, increased production of plant growth-promoting substances, and improved soil fertility. The study concludes that integrated application of Panchagavya and Jivamrita is an effective and sustainable nutrient management strategy for enhancing vegetative growth of knol-khol under Bundelkhand agro-climatic conditions.